Theory of the Death Drive as a Model for Speculative Philosophy: Land, Brassier, Negarestani, and Bataille - Tuomas, Linartas (Problemos, 2023)
This paper deals with Freud’s psychoanalytic theory of the death drive from the perspective of speculative philosophy. For this purpose, three philosophers have been chosen: Nick Land, Ray Brassier, and Reza Negarestani. I claim that they gradually radicalised the Freudian thought: Land expanded it to capitalist economy and terrestrial geotrauma; Brassier shifted it towards a solar catastrophe and the prospect of extinction; Negarestani incorporated it into the exteriority of cosmic contingency. This way, Freud’s legacy emerges as a transcendental, epistemological and speculative instrument to tackle Meillassoux’s problem of correlation. I consider why this trajectory has ceased: I suggest a hypothesis that Bataille’s influence has not been overcome, especially in the case of Negarestani. I offer several vectors, according to which, Bataille could serve as an opportunity for openness to the Outside and a chance to continue the trajectory of the speculative death drive. I suggest that it is possible to reconsider Bataille as one of the precursors to the contemporary speculative thought.